2019
DOI: 10.1108/ijoem-07-2017-0244
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of shocks between Chinese financial market and oil market

Abstract: Purpose The purpose of this paper is to empirically investigate the volatility spillover between the Chinese stock market, investor’s sentiment and oil market, specifically during the 2014‒2016 turmoil period. Design/methodology/approach This study used the daily and monthly China market price index, oil-price index and composite index of Chinese investor’s sentiment. The authors first use the DCC GARCH model in order to study the correlation between variables. Second, the authors use a continuous wavelet de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…More interestingly, the Nikkei225 of Brent is the strongest pairwise transmitter market of volatility shocks, while the Brent of CAC40 is the weakest. Undoubtedly, this can affect the Chinese economy and its impact is (Zhang and Chen, 2014;Chen, 2015;Luo and Ji, 2018;Abdelhedi and Boujelb ene, 2019). Moreover, we showed that the SP500-Gold pairwise exhibits a strong bidirectional connectedness, but has a weak connectedness with DAX stock markets.…”
Section: Network Connectednessmentioning
confidence: 76%
“…More interestingly, the Nikkei225 of Brent is the strongest pairwise transmitter market of volatility shocks, while the Brent of CAC40 is the weakest. Undoubtedly, this can affect the Chinese economy and its impact is (Zhang and Chen, 2014;Chen, 2015;Luo and Ji, 2018;Abdelhedi and Boujelb ene, 2019). Moreover, we showed that the SP500-Gold pairwise exhibits a strong bidirectional connectedness, but has a weak connectedness with DAX stock markets.…”
Section: Network Connectednessmentioning
confidence: 76%
“…Smyth and Narayan (2018) clearly emphasize upon the dearth of studies focusing on the developing countries that are witnessing an economical transitory phase, and their stock markets are at an embryonic stage, with only exception to China. In comparison to the other emerging countries, abundant literature is available that focusses upon the various aspects of the oil–stock relationship in China (Abdelhedi and Boujelbène-Abbes, 2020; Zhu et al , 2016). Withstanding China, limited number of studies can also be traced for other emerging countries, such as for Central and Eastern Europe (Asteriou and Bashmakova, 2013), India (Ghosh and Kanjilal, 2016), Russia (Bhar and Nikolova, 2010), African continent countries (Gupta and Modise, 2013), Brazil, Russia, India, China, and South Africa (BRICS) country group (Bagchi, 2017; Tiwari et al , 2019), Vietnam (Narayan and Narayan, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the existing literature, some of the researchers have utilized only gold prices (Arfaoui & Ben Rejeb, 2017;Shakil et al, 2018;Tuna, 2018) and others have utilized only oil prices (Lardic & Mignon, 2008;Sahu et al, 2014;Mollick & Nguyen, 2015;Wen et al, 2017;Abdel-Latif et al, 2018;Areli Bermudez Delgado et al, 2018;Pandey & Vipul, 2018;Kumar, 2019;A. Mouna, 2019;Narayan, 2019;Charfeddine & Barkat, 2020) in order to examine their linkages with stock market indexes.…”
Section: Research Gapsmentioning
confidence: 99%
“…In the existing literature, a number of research articles has explored symmetrical linkages between oil price volatility and stock indexes (Asad, 2011;Bagchi, 2017;Kisswani & Elian, 2017;Mongi, 2017;Roubaud & Arouri, 2018;Areli Bermudez Delgado et al, 2018;Husain et al, 2019;A. Mouna, 2019;Narayan, 2019;Nouira, Hadj Amor, & Rault, 2019) but limited efforts have been made to estimate oil price-stock price nexus asymmetrically (Kocaarslan & Soytas, 2019;Kumar, 2019;Charfeddine & Barkat, 2020;Chkir et al, 2020).…”
Section: Symmetrical-asymmetrical Relationship Between Oil Prices and Stock Indexesmentioning
confidence: 99%